Pengembangan Media Poster Edukasi pada Mata Pelajaran IPAS Kelas V SD Maccini Sombala - hajar nur aziza; Hotimah; Muhammad Rizah Putrawan (Universitas Islam Nahdlatul Ulama Jepara, 2026)
This study aims to develop an educational poster media based on QR Code for Grade V Science and Social Studies (IPAS) learning in elementary school. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects consisted of 1 media expert and 1 subject matter expert as product validators. In addition, the try-out was conducted with Grade V students of UPT SPF SD Maccini Sombala 1, consisting of one-to-one evaluation (1 student), small group trial (6 students), and large group trial (20 students). The classroom teacher was also involved as a respondent to assess the practicality of the developed learning media. The research instruments included observation sheets and interview guidelines used in the needs analysis phase, media expert validation questionnaires to assess design and visual aspects, material expert validation questionnaires to evaluate content accuracy and concept suitability, and response questionnaires for both teachers and students to measure the practicality of the media in classroom learning. The results showed that the educational poster media was categorized as highly feasible based on media and material expert validation. Furthermore, the one-to-one trial resulted in a highly practical category, the small group trial was also categorized as highly practical, and the large group trial confirmed the same category. In addition, teacher responses indicated that the media was highly practical in supporting IPAS learning activities in Grade V. Therefore, the QR Code-based educational poster media can be used as an alternative learning media for environmental topics in elementary schools.